2016
DOI: 10.3390/molecules21091216
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble-Bound Phenolics in Food

Abstract: Abstract:This contribution provides a review of the topic of insoluble-bound phenolics, especially their localization, synthesis, transfer and formation in plant cells, as well as their metabolism in the human digestive system and corresponding bioactivities. In addition, their release from the food matrix during food processing and extraction methods are discussed. The synthesis of phenolics takes place mainly at the endoplasmic reticulum and they are then transferred to each organ through transport proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
290
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 423 publications
(351 citation statements)
references
References 140 publications
5
290
0
15
Order By: Relevance
“…Bound phenolic compounds are not absorbed in the small intestine because they are ester‐linked to cell wall polysaccharides; they then enter the colon where they undergo fermentation by the colon microbiota giving rise to potentially absorbable metabolites (Shahidi and Yeo ). An in vivo animal study has shown that rat colonic microflora exhibit esterase activity that releases certain ferulic acid derivatives from dietary cereal bran which is later partially absorbed and then enters the circulatory system (Andreansen and others ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bound phenolic compounds are not absorbed in the small intestine because they are ester‐linked to cell wall polysaccharides; they then enter the colon where they undergo fermentation by the colon microbiota giving rise to potentially absorbable metabolites (Shahidi and Yeo ). An in vivo animal study has shown that rat colonic microflora exhibit esterase activity that releases certain ferulic acid derivatives from dietary cereal bran which is later partially absorbed and then enters the circulatory system (Andreansen and others ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the predominant phenolic acids in cereal grains such as corn are mostly hydroxycinnamic acid derivatives, which are found in insoluble bound forms linked to cell wall polysaccharides (Dewanto and others ; Guo and Beta ). This bound phenolic fraction is not absorbed in the small intestine and it reaches the colon where it is partially released by colon microbiota leading to a myriad of health benefits (Shahidi and Yeo ). In our previous study, the Peruvian purple corn accession AREQ‐084 had the highest total phenolic contents in its free and bound forms along with high total anthocyanin contents among different purple corn accessions (Huaman‐Alvino and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Os ácidos fenólicos solúveis ocorrem no vacúolo, conjugados ou não conjugados a outras substâncias. Existem também ácidos fenólicos insolúveis, que se encontram ligados à parede celular (Acosta-Estrada et al, 2014;Shahidi & Yeo, 2016). As concentrações dos ácidos fenólicos variam no mesmo órgão da planta e entre órgãos de uma mesma espécie.…”
Section: Iii1 Introduçãounclassified
“…A biossíntese de ácidos fenólicos solúveis e insolúveis se realiza no retículo endoplasmático; em seguida, são transferidos por vesículas de membranas para o vacúolo ou parede celular (Shahidi & Yeo, 2016). Os ácidos p-cumárico e ferúlico são os ácidos fenólicos majoritários da parede celular primária das gramíneas, o maior grupo do clado Commelinídea.…”
Section: Iii1 Introduçãounclassified
See 1 more Smart Citation